Evaluating voter perceptions of political party similarity: A mixed-method study of party positions in Taiwan - Shun-Chuan Chang (PLoS ONE, 2025)
This study examines voter perceptions of political party similarity using data from a validated online survey conducted in Taiwan. It primarily collects qualitative data through open-ended questions, complemented by Multiple Correspondence Analysis (MCA) and feature matching techniques. The findings reveal that party competition in Taiwan is multidimensional, extending beyond traditional blue-green and unification-independence divides. Notably, local Taiwanese issues and social concerns have become increasingly prominent among emerging third parties. Feature matching results show that 22.53% of respondents clearly distinguish the Taiwan People’s Party (TPP), while 11.42% identify the New Power Party (NPP), differentiating it from the pan-green camp as part of the emerging third force. Taiwan’s unique political context, shaped by democratization, cross-strait tensions, and the rise of influential third parties, provides valuable insights for comparative politics. The study offers an analytical framework for understanding party system evolution in emerging democracies and deepens our grasp of how identity politics and diverse political engagement transform political competition. This framework enables scholars to systematically capture complex voter perceptions in multi-party systems and facilitates comparative analysis across political environments marked by identity-based polarization and increasing party plurality.